APLICAÇÃO DE ANTIOXIDANTE NATURAL EM BIODIESEL - Pavanello, Guilherme Pozzobom (2017)
The incorporation of biodiesel in the Brazilian energy matrix resulted in an increase in the number of studies in relation to this biofuel. In 2014 there was an increase in the minimum limit required by the National Petroleum, Natural Gas and Biofuels Agency (NPA) for the parameter of oxidative stability. In response to the financial crisis in Brazil, the government adopted the increase of 1% of addition of biodiesel to diesel oil each year, until 2019, where this percentage will be 10%. Due to the biodegradability of biodiesel, synthetic antioxidants are added; however, they are toxic and carcinogenic. The aim of this study is to use the residue of candeia wood and vitamin E as antioxidants for biodiesel. Techniques were used such as: near infrared spectroscopy, scanning electron microscopy, test of oxidation accelerated (Rancimat® 873), analysis of density, electrical conductivity, pH, flash point, Karl Fischer method (water content) and the experimental planning was 2³. For use of the residue of candeia wood was used the acidic extraction and the vitamin E was added directly to biodiesel. The average result of acid extraction was that reduced 19,67% of initial mass of residual of candle. The best result for the test of oxidative stability of applied waste was 7.47 hours with concentration of 1.5 g.L-1. For vitamin E, it was 6.48 h when added to 500 ppm. When biodiesel was washed with a solution of residue 1,75 g.L-1 and added 200 ppm of vitamin E, the induction time of biodiesel was 8.91 h.